Advancements in the Use of Hydrogels for Regenerative Medicine: Properties and Biomedical Applications - Andrea Revete; Andrea Aparicio; Bruno A. Cisterna; Javier Revete; Luis Luis; Ernesto Ibarra; Edwin A. Segura González; Jay Molino; Diego Reginensi (International Journal of Biomaterials)
Due to their particular water absorption capacity, hydrogels are the most widely used scaffolds in biomedical studies to regenerate damaged tissue. Hydrogels can be used in tissue engineering to design scaffolds for three-dimensional cell culture, providing a novel alternative to the traditional two-dimensional cell culture as hydrogels have a three-dimensional biomimetic structure. This material property is crucial in regenerative medicine, especially for the nervous system, since it is a highly complex and delicate structure. Hydrogels can move quickly within the human body without physically disturbing the environment and possess essential biocompatible properties, as well as the ability to form a mimetic scaffold in situ. Therefore, hydrogels are perfect candidates for biomedical applications. Hydrogels represent a potential alternative to regenerating tissue lost after removing a brain tumor and/or brain injuries. This reason presents them as an exciting alternative to highly complex human physiological problems, such as injuries to the central nervous system and neurodegenerative disease.